Transparency and Accuracy: How Forensic Audits and Whistleblowers Create a Fraud-Free Business Environment - Setiawan, Rasyid; Khansa, Jeslyn Faiza; Pusvita, Hana; Ledi, Ledi; Suci, Rama Gita (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to investigate the critical roles of forensic audits and whistleblowers in creating a business environment free from fraudulent practices. Through an in-depth analysis of their respective contributions, this research seeks to provide a better understanding of how transparency and accuracy can form the foundation for establishing a more ethical and fraud-free business environment. The research method used in this article is qualitative. This type of research falls under a literature review study by examining 10 relevant journals discussing how forensic audits and whistleblowers contribute to creating a fraud-free business environment. The selection of these ten articles was carried out through a filtering process using inclusion and exclusion criteria. The study was compiled through a literature review, with sources accessed from various platforms, including national and international journal websites such as Google Scholar, PubMed, ScienceDirect, ProQuest, and Wiley.The results of this study indicate that transparency and accuracy are two main pillars in maintaining the integrity of the business environment. These principles are not only ethical guidelines but also the foundation for ensuring a business’s long-term success and sustainability. Forensic audits and whistleblowers are two key factors that play a vital role in fostering a fraud-free business environment.